2017
DOI: 10.1002/jbm.a.36228
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of osteogenic inductivity of a novel BMP2‐mimicking peptide P28 and P28‐containing bone composite

Abstract: We developed a novel BMP2-mimicking peptide P28, which possesses two distinct special structural elements-seven repetitive aspartic acids and phosphorylated serine designed to promote affinity to hydroxyapatite as well as nucleation of apatite crystallization and mineralization. In this work, we systematically studied the osteogenic inductivity of P28 in vitro and in vivo in comparison with BMP2. We confirmed its effects on proliferation, recruitment, and osteogenic differentiation of MC3T3-E1 cells in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…SIS/PLA was designed based on the principle of biomimetics, with both composition and structure being similar to natural bone. Its pore size of 100-300 mm may provide a superior structure: 25 macropores with a pore diameter in the range of 50-300 mm are required for cell penetration and neovascularization with a scaffold in vivo. Previous studies have demonstrated the outstanding biocompatibility and non-immunogenicity of SIS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SIS/PLA was designed based on the principle of biomimetics, with both composition and structure being similar to natural bone. Its pore size of 100-300 mm may provide a superior structure: 25 macropores with a pore diameter in the range of 50-300 mm are required for cell penetration and neovascularization with a scaffold in vivo. Previous studies have demonstrated the outstanding biocompatibility and non-immunogenicity of SIS.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the enhanced material retention and lower P28 concentration in bone tissue may improve the potency of P28 in exerting osteogenic bioactivity used in our previous study. 25 We then focused on verifying the biological activity of P28 and PlGF-2 123-144* fused P28 in subsequent cell and animal experiments. The effects of the scaffold material on cell behavior are a result of the interactions between the ligand on the scaffold surface and the receptors on the cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, P28 content was determined using high-performance liquid chromatography, as previously described. 27 To investigate the release kinetics of P28, mSIS/P28 (5×5×0.5 mm 3 ) with or without heparinization was incubated in 200 mL PBS at 37°C for 14 days. The eluted P28 peptide was quantified at day 0.5, 1, 3, 5, 7, 10, 14, 17, 21, 25, 29, 33, and 37 following incubation.…”
Section: Immobilization Efficacy Of P28 On Membranes and Its Release mentioning
confidence: 99%
“…ARS staining was performed according to a previous study. 27 The optical density of Alizarin Red extracted from the samples was spectrophotometrically determined at 405 nm wavelength using a microplate reader.…”
Section: Isolation and Characterization Of Bone Marrow Stromal Stem Cmentioning
confidence: 99%